Diseases of white sea bream (Diplodus sargus L.) reared in experimental and commercial conditions in Greece - Golomazou, E.; Athanassopoulou, F.; Vagianou, S.; Sabatakou, O.; Tsantilas, H.; Rigos, G.; Kokkokiris, L. (2006)
A bacteriological and parasitological study of the white sea bream, Diplodus sargus L., was conducted as this species is a potential candidate for aquaculture in Mediterranean countries. The study comprised fish reared in commercial cages (2 farms) located in different geographical localities, as well as fish reared experimentally in cages located in a natural enclosed lagoon. Fish were examined in the fresh state by means of smears from all internal and external organs and by histology. Microbiology was also performed at all sites. Mortality was low (12%) at farm 1 (Argolida), while at farm 2 (Korinth) and the lagoon it reached 32% and 42%, respectively. Microbial infections were low in prevalence and these concerned Vibrio anguillarum, V. alginoliticus and Pseudomonas sp. The parasitic fauna comprised external Monogenea, Digenea and internal Myxosporida. Monogenea were present throughout the year at all locations, but at low intensity. Three species of Myxosporida were recorded in this study: Myxobolus sp. in the kidneys, Kudoa sp. in the musculature and Enteromyxum leei in the intestine. Nephrocalcinosis was found in all sampled fish and this was suspected to be related to Myxobolus sp. infections. The study showed that D. sargus reared under captive conditions is prone to several parasitic and bacterial infections. Amongst them the most important in terms of pathology were the myxosporeans (Myxobolus sp. and Kudoa sp). These may play a role in the mortality observed, thus making this fish culture questionable in terms of cost effectiveness.